2021
DOI: 10.1038/s41541-021-00407-3
|View full text |Cite
|
Sign up to set email alerts
|

Malaria transmission-blocking conjugate vaccine in ALFQ adjuvant induces durable functional immune responses in rhesus macaques

Abstract: Malaria transmission-blocking vaccines candidates based on Pfs25 and Pfs230 have advanced to clinical studies. Exoprotein A (EPA) conjugate of Pfs25 in Alhydrogel® developed functional immunity in humans, with limited durability. Pfs230 conjugated to EPA (Pfs230D1-EPA) with liposomal adjuvant AS01 is currently in clinical trials in Mali. Studies with these conjugates revealed that non-human primates are better than mice to recapitulate the human immunogenicity and functional activity. Here, we evaluated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Accordingly, Pfs230 is the most clinically advanced TBV candidate, with Pfs230D1M-EPA/Alhydrogel showing superior clinical efficacy to Pfs25 in comparative studies in humans and Rhesus macaques . 20 , 54 Importantly, the humoral response to gametocyte TBV immunogens such as Pfs230 may be reinforced by prior and/or subsequent natural infection. 55 Humoral responses against Pfs230 are common in malaria endemic regions, 56 , 57 and we have recently shown that affinity-purified Pfs230-specific antibodies can indeed block transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Pfs230 is the most clinically advanced TBV candidate, with Pfs230D1M-EPA/Alhydrogel showing superior clinical efficacy to Pfs25 in comparative studies in humans and Rhesus macaques . 20 , 54 Importantly, the humoral response to gametocyte TBV immunogens such as Pfs230 may be reinforced by prior and/or subsequent natural infection. 55 Humoral responses against Pfs230 are common in malaria endemic regions, 56 , 57 and we have recently shown that affinity-purified Pfs230-specific antibodies can indeed block transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond antigen stabilization, vaccine formulation—both in terms of multivalent antigen display and adjuvant selection—is a major component of subunit vaccine design. Several display platforms exist and have been used for TBV antigen presentation, including genetic fusions and affinity linkages ( Brod et al., 2018 ; Chichester et al., 2018 ; Mabrouk et al., 2020 ; Scaria et al., 2020 , 2021 ; Jardine et al., 2013 ; Huang et al., 2018 , 2020 ; Mabrouk et al., 2021 ). An advantage of the CPQ platform used in the present study is its ability to easily incorporate antigenic designs along with adjuvants for rapid immunogenicity screening.…”
Section: Discussionmentioning
confidence: 99%
“…Both vaccine conjugates generated strong antibody responses after two vaccinations. Although functional activity declined rapidly, a third vaccination of Pf s230D1-EPA induced functional activity which lasted for a few months ( 144 ).…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%